Sustainable Branding : Empowering SMEs Through Digital Marketing Strategies - Ardi Armen (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This research aims to explore sustainable digital marketing strategies for Micro, Small, and Medium Enterprises (MSMEs) with a focus on redefining brand identity. The research employs a qualitative approach, utilizing in-depth interviews and thematic analysis. A purposive sampling technique is employed to select participants from diverse MSME backgrounds. Through rigorous thematic analysis, the study reveals insights into effective digital marketing strategies that align with sustainability goals while reshaping brand identities for MSMEs. The findings highlight the importance of authenticity, transparency, and social responsibility in crafting sustainable brand identities in the digital era. This research contributes to the understanding of practical strategies for MSMEs to thrive in the competitive digital marketplace while embracing sustainability principles.